Harnessing Migration for Inclusive Growth and Development in Southern Africa - Crush, Jonathan, 1953-; Tevera, Daniel S.; Williams, Vincent; Dodson, Belinda (Special report (Southern African Migration Programme), 2017)
The primary goal of this study is to present the results of a comprehensive scope of key opportunities and challenges for harnessing migration for inclusive growth and development at the regional level in Southern Africa. The main objectives were as follows: Provide an overview of regional migration stocks and flows identifying regional trends, drivers and impacts from existing research literature and official data; Profile migrant characteristics at the regional level including demographic composition, types of migration and occupational profile; Examine the relevance of multilateral, continental and regional migration instruments, policies, protocols, agreements and forums with a view to identifying actions required to move the regional migration management agenda forward and align with the goal of enhancing migration for inclusive growth and development in Southern Africa; Analyze the key initiatives, opportunities and obstacles to developing a coherent, integrated and rights-regarding approach to migration management including areas of common commitment and ownership, and points of actual and potential conflict and disagreement between states; Conduct a gender analysis of regional migration dynamics including gender dimensions of migration, challenges, dangers and vulnerabilities confronting migrant women and other vulnerable groups, and gender analysis of migration management in Southern Africa; Identify potential programming areas that are weak or underdeveloped.